Pengaruh Kedisiplinan dan Lingkungan Kerja terhadap Kinerja Karyawan pada PT Permodalan Nasional Madani Cabang Palmerah Jakarta : Penelitian - Jeje Juwita; Sheila Ardilla Yughi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to determine the influence of discipline and work environment on employee performance at PT Permodalan Nasional Madani Palmerah Branch, Jakarta. The research method uses quantitative methods through an associative approach. The population in this study was 60 respondents. The sampling technique used is the Nonprobability Sampling or Saturated Sampling technique. The analysis in this research used the SPSS (Statistical Package for Social Science) software program version 23.0. The results of research on the Discipline variable (X1) show that there is a partial influence of discipline on employee performance. Based on the results of the t test (partial test) on the Discipline variable (X1) which shows the value of tcount > ttable and significant < 0.05, namely; 6.631 > 2.001 and significant 0.000 < 0.05. The Work Environment variable (X2) shows that there is a partial influence of the work environment on employee performance. Based on the results of the t test (partial test) on the Work Environment variable (X2) which shows the tcount > ttable and significant < 0.05, namely; 16.765 > 2.001 and significant 0.000 < 0.05. Simultaneous results show that there is an influence of discipline and work environment on employee performance simultaneously. Based on the results of the F test (simultaneous test) on the Discipline (X1) and Work Environment (X2) variables which show the tcount > ttable and significant < 0.05, namely; 141.359 > 3.16 and significant 0.000 < 0.05. Based on the results of the coefficient of determination test, the Adjusted R Square value is 0.826 or 82.6%. This means that the Discipline (X1) and Work Environment (X2) variables are able to explain the magnitude of the influence on the Employee Performance variable (Y) by 82.6% while the remaining 17.4% is influenced by other variables.